2014
DOI: 10.1002/jbio.201400040
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy of serum: A study on ‘pre’ and ‘post’ breast adenocarcinoma resection in rat models

Abstract: Risk of recurrence is a major problem in breast cancer management. Currently available prognostic markers have several disadvantages including low sensitivity and specificity, highlighting the need for new prognostic techniques. One of the candidate techniques is serum-based Raman spectroscopy (RS). In this study, feasibility of using RS to distinguish 'pre' from 'post' breast tumor resection serum in rats was explored. Spectral analysis suggests change in proteins and amino acid profiles in 'post' compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
2
1
0
Order By: Relevance
“…Interestingly, although NR serum exhibits differences in post‐surgery serum biochemical profile compared to R subjects, the AS serum of NR is not identical to H serum with respect to its biochemical composition. A previous study has also shown similar findings in mouse models for breast cancer 37 . In the present study, greater DNA and protein content were observed in the NR serum compared to H serum.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, although NR serum exhibits differences in post‐surgery serum biochemical profile compared to R subjects, the AS serum of NR is not identical to H serum with respect to its biochemical composition. A previous study has also shown similar findings in mouse models for breast cancer 37 . In the present study, greater DNA and protein content were observed in the NR serum compared to H serum.…”
Section: Discussionsupporting
confidence: 91%
“…A previous study has also shown similar findings in mouse models for breast cancer. 37 In the present study, greater DNA and protein content were observed in the NR serum compared to H serum. Lower beta-carotene content was observed in NR serum compared to H serum, from the difference spectrum.…”
Section: Raman Spectral Analysessupporting
confidence: 51%
“…Spectroscopy is a promising method for fast and reliable diagnostics in nonlaboratory settings . Raman spectroscopy has the major advantage of being rather unsusceptible to aqueous environments , because the Raman cross-section of water is relatively small . Furthermore, Raman measurements require less sample preparation and no complex laboratory infrastructure.…”
mentioning
confidence: 99%